Metabolic Engineering of Escherichia coli for Ectoine Production With a Fermentation Strategy of Supplementing the Amino Donor - Zhang, Hao; Liang, Zhong; Zhao, Ming; Ma, Yanqin; Luo, Zhengshan; Li, Sha; Xu, Hong (Frontiers in Bioengineering and Biotechnology, 2022)
Ectoine, an osmotic pressure-compensated solute, is used in the food, agriculture, medicine, and cosmetics industries due to its ability to protect macromolecules . In this study, an ectoine-producing variant of Escherichia coli, ET08, was genetically constructed by introducing the ectABC gene cluster and eliminating metabolic pathways involving lysine and pyruvate. Medium optimization enhanced ectoine production from 1.87 to 10.2 g/L. Analysis of the transcriptional levels revealed that supplementation with ammonium sulfate enhanced the metabolic flux towards the biosynthesis of ectoine. Furthermore, by optimizing the copy number of ectA, ectB and ectC, the recombinant E. coli ET11(ectA : ectB : ectC = 1: 2: 1) produced 12.9 g/L ectoine in the shake flask and 53.2 g/L ectoine in a fed-batch fermenter, representing the highest ectoine titer produced by E. coli, which has great industrial prospects.